COUP-TFII Is Preferentially Expressed in the Caudal Ganglionic Eminence and Is Involved in the Caudal Migratory Stream - Kanatani, Shigeaki (J Neurosci, 2008)
While the cortical interneurons derived from the medial ganglionic eminence (MGE) migrate rather diffusely into the cortex, interneurons that migrate out from the caudal ganglionic eminence (CGE) mainly move caudally into the caudal cerebral cortex and the hippocampus in the form of the caudal migratory stream (CMS) (Yozu et al., 2005). Although transplantation experiments at embryonic day 13.5 had revealed that the migrating cells in these two populations are already intrinsically different in regard to their ability to respond to the CGE environment (Yozu et al., 2005), it is not known how the CGE cells are specified and how their migratory behavior is determined. In this study we showed that, although CGE and lateral ganglionic eminence (LGE) express almost the same marker molecules, LGE cells do not migrate caudally when transplanted into the CGE, suggesting that LGE cells are intrinsically different from CGE cells. We therefore compared the transcriptomes of the CGE, MGE, and LGE, and the results showed that COUP-TFII was expressed preferentially in the CGE as well as in the migrating interneurons in the CMS. Transplantation experiments revealed that COUP-TFII is sufficient to change the direction of MGE cell migration to caudal when transplanted into the CGE environment, and knockdown of COUP-TFII inhibited the caudal migration of the CGE cells. These results suggest that COUP-TFII is both required and sufficient for the CGE-cell-specific migratory behavior in the caudal direction. Thus, a locally expressed transcription factor determines the migratory direction of the cortical interneurons in a region-specific manner.